Optimalisasi Keterlibatan Sumber Daya Manusia Madrasah dalam Upaya Pencegahan Perundungan di MTsN 1 Bireuen - Zulfikar, Zulfikar; Ali Buto, Zulfikar; Barus, Jumat (Indonesian Journal of Islamic Educational Management, 2024)
The cases of bullying still continue to occur in the world of education, so the role of human resources in madrasas is very much needed as an effort to prevent it. This research aims to analyze and describe the role of human resources in cases of bullying, and optimize the involvement of human resources in efforts to prevent bullying at MTsN 1 Bireuen. This research is a qualitative descriptive study with data collection techniques through observation, in-depth interviews and documentation. The research subjects were madrasa heads, teachers, guidance and counseling teachers, and deputy madrasa heads for student affairs. Meanwhile, the data analysis technique goes through three stages, namely data reduction, data display and conclusion drawing. The research results show that madrasa heads, teachers, guidance and counseling teachers and student representatives have a role in efforts to deal with bullying in madrasas. The madrasa head carries out planning, supervision and evaluation. Teachers educate students in character building through learning and providing advice to students. Counseling teachers become leaders on the issue of bullying. Meanwhile, student representatives coordinate with various parties. Optimization was carried out by the madrasa head, teachers and student representatives at MTsN 1 Bireuen by participating in socialization about bullying in madrasas by resource persons. Meanwhile, BK teachers learn independently through the Ministry of Religion's Smart Online application